Stress-Tunable Spin-Wave Dynamics in Superellipse-Shaped Fega Nanostructures - Escrig-Murua, J; Saavedra-Díaz, E (American Institute of Physics, 2025)
Through micromagnetic simulations, we investigate the high-frequency dynamic properties of FeGa nanostructures with superellipse geometries, focusing on the dynamic susceptibility and the spatial profiles of the resonant modes under stress-induced anisotropy. Two distinct equilibrium states are identified: an in-plane magnetic configuration aligned along the x-axis and a vortex configuration. The results reveal a direct correlation between the number and frequencies of resonant modes and the minimum energy magnetic state, both governed by the system s physical parameters. These findings offer insights for the design of stress-tunable, high-frequency magnetic microwave devices. © 2025 Author(s).